Job Search and Hiring with Limited Information about Workseekers’ Skills - Carranza, Eliana; Garlick, Robert; Orkin, Kate; Rankin, Neil (American Economic Review, 2022)
We assess South African workseekers’ skills and disseminate the assessment results to explore how limited information affects firm and workseeker behavior. Giving workseekers assessment results that they can credibly share with firms increases workseekers’ employment and earnings and better aligns their skills, beliefs and search strategies. Giving workseekers assessment results that they cannot easily share with firms has similar effects on beliefs and search, but smaller effects on employment and earnings. Giving assessment results only to firms shifts interview decisions. These findings show that getting credible skill information to the right agents can improve outcomes in the labor market. (JEL J22, J23, J24, J31, J41, J64, O15)